AlyBase: database of names, chromosome numbers, and ploidy levels of Alysseae (Brassicaceae), with a new generic concept of the tribe - S̆paniel, Stanislav; Kempa, Matúš; Salmerón-Sánchez, Esteban; Fuertes-Aguilar, Javier; Mota, Juan F.; Al-Shehbaz, Ihsan A.; German, Dmitry; Olšavská, Katarína; Šingliarová, Barbora; Zozomová-Lihová, Judita; Marhold, Karol (Plant systematics and evolution, 2015)
Database of published chromosome numbers and ploidy-level estimates of the tribe Alysseae is presented, together with the revised generic concept and the list of accepted names, to reflect the most recent taxonomic and phylogenetic studies in Alysseae. It is available on-line at www.alysseae.sav.sk. The tribe encompasses 24 genera and 277 species. Chromosome numbers and/or ploidy levels are known for 171 out of 297 recognized taxa. Of these, 95 (55.6 %) taxa are diploids, 43 (25.1 %) are polyploids, and 33 (19.3 %) involve both diploids and polyploids. The most common base chromosome number in the tribe is x = 8 and less frequent is x = 7. The highest variation in base chromosome numbers (x = 7, 8, 11, 15) is found in the genus Hormathophylla. A key to all genera and descriptions of the two new genera Cuprella and Resetnikia are presented. Many new nomenclatural combinations, mainly in the re-established Odontarrhena (77), are proposed.
Gesehen am 19.06.2020